Embryonic Photosynthesis Affects Post-Germination Plant Growth . Issue 4 (14th February 2020) - Sela, Ayala; Piskurewicz, Urszula; Megies, Christian; Mène-Saffrané, Laurent; Finazzi, Giovanni; Lopez-Molina, Luis
Abstract : Perturbing embryonic photosynthesis compromises post-germinative growth and development of Arabidopsis. Abstract: Photosynthesis is the fundamental process fueling plant vegetative growth and development. The progeny of plants relies on maternal photosynthesis, via food reserves in the seed, to supply the necessary energy for seed germination and early seedling establishment. Intriguingly, before seed maturation, Arabidopsis ( Arabidopsis thaliana ) embryos are also photosynthetically active, the biological significance of which remains poorly understood. Investigating this system is genetically challenging because mutations perturbing photosynthesis are expected to affect both embryonic and vegetative tissues. Here, we isolated a temperature-sensitive mutation affecting CPN60α2, which encodes a subunit of the chloroplast chaperonin complex CPN60. When exposed to cold temperatures, cpn60α2 mutants accumulate less chlorophyll in newly produced tissues, thus allowing the specific disturbance of embryonic photosynthesis. Analyses of cpn60α2 mutants were combined with independent genetic and pharmacological approaches to show that embryonic photosynthetic activity is necessary for normal skoto- and photomorphogenesis in juvenile seedlings as well as long-term adult plant development. Our results reveal the importance of embryonic photosynthetic activity for normal adult plant growth, development, and health.